On the Projections of the Mutual Multifractal Rényi Dimensions (Analysis in Theory and Applications, 2021)
In this paper, we compare the mutual multifractal Rényi dimensions to the mutual multifractal Hausdorff and pre-packing dimensions. We also provide a relationship between the mutual multifractal Rényi dimensions of orthogonal projections of a couple of measures $(μ, u)$ in $\mathbb{R}^n$. As an application, we study the mutual multifractal analysis of the projections of measures.